الثقة التنظيمية وعلاقتها بالالتزام التنظيمي - بوعنان حياة (Universty Of El-oued جامعة الوادي, 2024)
الملخص: جاءت هذه الدراسة بهدف التعرف على العلاقة بين الثقة التنظيمية والالتزام التنظيمي لدى العاملين الإداريين بجامعة الشهيد حمة لخضر بالوادي، وذلك انطلاقا من التساؤل الرئيسي:هل توجد علاقة ارتباطية بين الثقة التنظيمية والالتزام التنظيمي لدى العاملين بجامعة الشهيد حمة لخضر بالوادي؟ وينطلق من السؤال العام الأسئلة الجزئية التالية: هل توجد علاقة ارتباطية بين الثقة بالمشرف المباشر والالتزام التنظيمي لدى العاملين الاداريين بجامعة الوادي؟ هل توجد علاقة ارتباطية بين الثقة بزملاء العمل والالتزام التنظيمي لدى العاملين الاداريين بجامعة الوادي؟ هل توجد علاقة ارتباطية بين الثقة ببيئة العمل المادية والالتزام التنظيمي لدى العاملين بجامعة الوادي؟ هل توجد علاقة ارتباطية بين الثقة بالحوافز والالتزام التنظيمي لدى العاملين بجامعة الوادي؟ فقد تم الاعتماد على المنهج الوصفي التحليلي. ولجمع البيانات من الميدان تم تطبيق أداة الاستبيان كأداة رئيسية، حيث طبقت على العاملين الاداريين بجامعة الوادي وقدر عددهم(200) مفردة، باستخدام أسلوب المسح الشامل. أسفرت الدراسة على جملة من النتائج نذكرها كالتالي: توجد علاقة ارتباطية بين الثقة التنظيمية والالتزام التنظيمي لدى العاملين الاداريين بجامعة الوادي، ونستدل على ذلك بقيمة معامل الارتباط(r=0.315) وهو دال احصائيا عند مستوى الدلالة(0.05). توجد علاقة ارتباطية بين الثقة في المشرف المباشر والالتزام التنظيمي لدى العاملين الاداريين بجامعة الوادي، ونستدل على ذلك بقيمة معامل الارتباط (0.236) وهو دال احصائيا عند مستوى الدلالة (0.05). لا توجد علاقة ارتباطية بين الثقة في زملاء العمل والالتزام التنظيمي لدى العاملين الاداريين بجامعة الوادي، ونستدل على ذلك بقيمة معامل الارتباط (0.124) وهو غير دال احصائيا عند مستوى الدلالة (0.05). توجد علاقة ارتباطية بين الثقة في بيئة العمل المادية والالتزام التنظيمي لدى العاملين الاداريين بجامعة الوادي، ونستدل على ذلك بقيمة معامل الارتباط (r=0.153) وهو دال احصائيا عند مستوى الدلالة (0.05). توجد علاقة ارتباطية بين الثقة في الحوافز والالتزام التنظيمي لدى العاملين الاداريين بجامعة الوادي، ونستدل على ذلك بقيمة معامل الارتباط (r=0.182) وهو دال احصائيا عند مستوى الدلالة (0.05). Résumé : فرنسية أو انجلزية This study is intended to identify the link between organizational confidence and organizational commitment among administrative workers at the University of Martyr Hama Lakhdar in El Oued، based on the main question: -Is there a link between organizational confidence and organizational commitment among administrative workers at the University of Martyr Hama Lakhdar El Oued? Under this general question، the following sub-questions include: - Is there a correlation between trust in the direct supervisor and organizational commitment among administrative workers at El Oued University? - the link between organizational confidence and organizational commitment among administrative workers at El Oued University? Is there a correlation between confidence in the physical work environment and organizational commitment among administrative workers at El Oued University? - Is there a correlation between confidence in incentives and organizational commitment among administrative workers at El Oued University? According to the nature of the subject، a descriptive and analyzing information from the fuild, the survez mean was used، and to collect data from the field، the questionnaire tool was applied as the main tool. It was applied to the administrative workers at the University of El Qued، and their number was estimated at 200 individuals using the comprehensive survey method. consequences of the study are significant consequences، containing: -There is alink correlation between organizational confidence and organizational commitment among administrative workers at El Oued University This appears clearly in the value of the link coefficient(r= 0,315) which is statistically significant at the level of significance(0,05). -There is a link correlation between confidence in the direct supervisor and organizational commitment among administrative workers at El Oued University,and we infer that by the value of the correlation coefficien(r= 0,236)، which is statistically significantat the level of significance(0.05). -There is no correlation between trust in co-workers and organizational commitment among administrative workers at El Oued University, and we infer that by the value of the correlation coefficient(r= 0,124) which is not statistically significantat the level of significance(0.05). -There is a link correlation between confidence in the physical work environment and organizational commitment among administrative workers at El Oued University، and we infer that by the value of the correlation coefficient(r= 0,153), which is statistically significantat the level of significance(0.05). -There is a link correlation between confidence in Incentives and organizational commitment among administrative workers at El Oued University,and we infer that by the value of the correlation coefficient(r= 0,182)، which is statistically significantat the level of significance(0.05).
دراسة ميدانية لدى العاملين الإداريين بجامعة الشهيد حمة لخضر بالوادي
أطروحة دكتوراه تخصص: علم الإجتماع المنظمات والاتصال والموارد البشرية في العلوم الإجتماعية و الإنسانية
Keywords: الثقة التنظيمية- الالتزام التنظيمي- العاملين الاداريين; organizational trust- organizational commitment-administrative personnel.